Analisis Kesulitan Kemampuan Berpikir Logis dalam Pembelajaran IPA yang Dihadapi Siswa Pendidikan Dasar - Yanti Fitria; Adam Malik (Postgraduate, University of Mataram, 2022)
Logical thinking is analyzing a situation and coming up with a reasonable solution. It is crucial because it can help a person reason through crucial decisions, solve problems, generate creative ideas, and set goals to be achieved, all of which are needed to develop self-competence. This study aims to explain students' difficulties in logical thinking ability in elementary education on a natural science course. This study is qualitative using the literature review technique about students' difficulties in logical thinking. The results of the analysis have shown that the difficulties faced by students in developing logical thinking ability are in determining alternatives for the problems given; choosing and solving problems in natural science given by lecturers, and in students to understand. The causes of students having difficulties in developing logical thinking are not used to solving problems in natural science that need logical thinking. In addition, students are less creative in choosing or looking for the right strategy for the problems given. Finally, students are less thorough in solving problems in natural science